(3GdQhVI GdQjG ajef Oaf HOGQjGs - (3YHO GdQMef Hf eMeO Hf eMeO GdYeGOj GdMfaj GdOeTbj,J (B1051 (3g` s ((3jMji Hf RcQjG GdTHdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fhY dgPg GdCeI CSHGH GdNjQGJ s
(3GfXQ Qbe (B269 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B191s
Keywords: (3GdJGQjNs